Psychotherapy and Ketamine: How Does This Combination Affect the Duration of the Antidepressant Effect? - Zaika, Viacheslav; Tytarenko, Yan (Psychosomatic Medicine and General Practice, 2026)
Background. Ketamine provides rapid but short-lived antidepressant effects for treatment-resistant depression (TRD). To prolong this response, ketamine-assisted therapy (KAT) combines the drug’s pharmacological effects with psychotherapy. Aim. This study aims to analyze scientific evidence regarding the synergistic interaction between ketamine’s pharmacological effects and modern psychotherapeutic interventions, viewing the drug’s effect as a foundation for therapy. Materials and Methods. A review of scientific literature, including randomized controlled trials, open-label studies, and systematic reviews, was conducted to evaluate combining ketamine with psychotherapy. Results. Evidence shows that structured approaches like cognitive-behavioral therapy (CBT), behavioral activation (BA), and automated computer training of implicit self-associations (ASAT) may moderately prolong ketamine’s antidepressant effects, though data are heterogeneous. However, one study showed no clear advantage of ASAT combined with psychotherapy over ketamine monotherapy. Synergism may theoretically rely on utilizing a ketamine-induced “window of heightened neuroplasticity” to consolidate new cognitive-emotional and behavioral patterns. Conclusions. Current scientific data require further accumulation and structuring to develop standardized KAT protocols. Large, well-designed RCTs are necessary to definitively confirm how much psychotherapy contributes to prolonging ketamine’s antidepressant efficacy. Keywords: Ketamin, psychotherapy, depression, ketamin-assisted therapy, psychedelic-assisted therapy, antidepressants